Syn-eruptive sedimentation in the Hualcupén Formation: paleoenvironmental evidence from the Pliocene-Pleistocene period, Caviahue, Neuquén (Latin American Journal of Sedimentology and Basin Analysis, 2026)
The Hualcupén Formation constitutes the basal unit of the Pliocene-Recent Caviahue-Copahue Volcanic Complex (CCVC), located in the Southern Volcanic Zone (Fig. 1) to the north of the Patagonian Andes (37°50´S – 71°00´W). In plan-view, the complex is a rectangular depression up to 14 km wide and 18 km long, known as the Bajo del Agrio (Groeber, 1925) or Agrio/Caviahue Caldera (Pesce, 1989). The Pliocene-Pleistocene Hualcupén Formation (Muñoz Bravo et al., 1989; Linares et al., 1999; Sruoga and Consoli, 2011a) comprises a succession of effusive and explosive volcanic rocks interbedded with sedimentary units (Pesce, 1989; Varekamp et al., 2006), exposed along the caldera walls. Although the unit has been mentioned in regional studies, a detailed analysis of its deposits to comprehensively understand the relationship between volcanic and sedimentary processes in a paleoenvironmental context has been lacking. Through a detailed facies and depositional process analysis of the lower Hualcupén Formation, the main goals were to: (i) analyze the stratigraphy and sedimentology of the lower section of the succession, (ii) elucidate the interplay between volcanic and sedimentary processes, and (iii) interpret the paleoenvironmental conditions during deposition. The unit was initially defined by González and Vergara (1962) in Chile as the Cola de Zorro Formation, with Pesce (1989) assigning the name Hualcupén Formation for the equivalent Argentine unit, referring to the volcanic complex's basal unit. Lithologically, it has thicknesses between 400 and 800 m constituted by successions of potassium-rich andesites and basaltic andesites with intercalations of volcanic agglomerates (Pesce, 1989). Furthermore, Mazzoni and Licitra (2000) estimated a predominance of debris flow conglomeratic deposits in the middle-lower parts of the unit, while Mazzoni (1998) recognized a dominance of pyroclastic flow deposits in the middle to upper sections of the unit.Five informal stratigraphic sections were identified on a large scale within the Hualcupén Formation, outcropping on the eastern caldera wall (37°50'52.04"S – 70°57'32.09"W; Fig. 2). Detailed analysis was conducted on the lower stratigraphic sections (sections 1 and 2; Fig. 3). Within these, sedimentary, pyroclastic, and lava facies were defined, which were subsequently grouped into five facies associations (FA1 to FA5; Fig. 4). FA1 (Figs. 4 and 5) is composed predominantly of tabular conglomeratic bodies (Gmm1 and Gmm2 facies) and, to a lesser extent, fine-grained facies towards the tops of the conglomerates (Fm/Fl facies). The presence of massive conglomeratic facies, matrix-supported texture, a sandy-clayey silty clastic matrix, and poor sorting indicate paleoenvironmental conditions dominated by debris flows (Smith, 1986) with occasional flow waning. These characteristics are consistent with lahar-related deposits; however, the absence of clear diagnostic features prevents distinguishing between primary (syn-eruptive), secondary (post-eruptive), or non-eruptive lahars (Reading, 1998; Németh and Martin, 2007). FA2 (Figs. 4 and 6) is composed predominantly of lenticular conglomeratic bodies (GCgn, GCm1, GCm2, GC, GCi facies) with minor participation of tabular bodies of pebble sandy facies (GRm) and sandy facies (Sm/Sh). This facies association is dominated by massive to graded deposits, with moderate sorting, and to a lesser extent, deposits with tractive structures, indicating the dominance of hyperconcentrated flows with subordinate participation of debris flows and dilute aqueous flows (Smith, 1986; Reading, 1998; Capra et al., 2004; Németh and Martin, 2007). They suggest conditions similar to FA1 but with a greater water-sediment ratio, allowing interpretation as lahar deposits. FA3 (Figs. 4 and 7) is generally composed of lenticular, erosive-based conglomeratic bodies (GC facies) and pebble sandstone deposits (Gp-GRp, Gh-GRh facies). The dominance of clast-supported textures and moderate to good sorting indicates the presence of dilute aqueous flows with a low proportion of hyperconcentrated flows. This facies association can be linked to alluvial-fluvial processes, whose deposits collectively constitute the infill of a channel, indicating a decrease in the energy of the transporting agent from base to top. FA4 (Figs. 4 and 8) is composed mostly of breccia bodies (mlBr and mlBrp facies) and massive lapilli tuffs (mLT1 and mLT2 facies). The textural characteristics and the presence of pumice allowed the interpretation that these facies association corresponds to deposits accumulated from concentrated pyroclastic density currents (PDC), with the presence of a basal flow with a higher lithic concentration (mlBr and mlBrp facies; Druitt, 1998; Branney and Kokelaar, 2002; Sulpizio et al., 2014; Cas et al., 2024). FA5 (Figs. 4 and 9) is represented by lava facies (Lvm, Lvc1 and Lvc2) that form a single body with a lenticular base and a flat top. This facies association is considered to result from a lava flow with structures and fractures related to rapid cooling, such as columnar jointing and cube-jointing structure.The analysis of these facies associations allowed for the interpretation and discussion of the depositional environment. The lower section of the Hualcupén Formation (sections 1 and 2) is dominated by sedimentary processes, pyroclastic activity, and lava flows, resulting in purely sedimentary, volcanic, and volcano-sedimentary interaction deposits. Based on paleocurrent data (Fig. 3), it was established that the source and discharge areas were located to the west and east, respectively. The analyzed succession was accumulated in an environment in which sedimentary and volcanic processes predominated, with periods of syn-eruptive sedimentation. Section 1 (encompassing FA1, FA2, FA3, and FA4) is dominated by sedimentary reworking of volcanic products, mainly debris flows with subordinate hyperconcentrated to dilute aqueous flows. The intercalation of primary volcanic deposits allows interpretation of this section as recording a syn-eruptive sedimentation stage. In adittion, Section 2 (represented by FA4 and FA5) is composed exclusively of primary explosive and effusive volcanic products, indicating an increase in volcanic activity through time that may have led to the drowning of sedimentary systems due to the overwhelming influx of volcanic material. Finally, the wide regional distribution of these deposits implies that the deposition of this unit cannot be linked to the construction of a single volcanic edifice with a central conduit (like the typical stratovolcanoes of the adjacent arc). Instead, it was possibly related to a volcanic field or a compound volcanic massif associated with sedimentary processes. These processes indicate landscapes with high relief and dominant gravitational flows, likely associated with the development of the Andean volcanic arc and its surrounding region.
Keywords: hyperconcentrated flows; debris flows; lahars; volcanic stratigraphy